Comparative study of the ulcerogenico effect of single doses of celecoxib, ibuprofen and indomethacin in rats albins - Ramírez C., Francisco J. (2008)
The ulcerogénic capacity as a single oral dose of three nonsteroidal anti·inflammatory drugs (NSAIDs) of ample use in Therapeutic as they are celecoxib, ibuprofeno and indometacina was evaluated. Eight (08) male rats were dis tributed in four groups. Animals fasting during 24h previous to experiment. Group 1: lndomethacin was administrated 15 mg/kg oral dose. Group 2: Ibuprofen 100 mg/kg oral dose. Group 3: Celecoxib 100mg/kg/oral dose. Group4: physiological serum (Control). Macroscopic evaluation of small intestine (jejunum-ileum) were carried out at first day after drug administration. Intestinal injury were observed a long the mesenteric si de of the middle and distal jejunum. Macroscopic lesions consisted of bowel thickening and dilatatíon, absence of the mucosa, hyperemia and multiple round ulcers. The treatment with celecoxib was the one that displayed minor damage. The greater degree of injury was observed in the treatment with indomethacin. In the gas trie mucosa the greater damage was observed in the treatments with indomethacin and ibuprofen.